Practical clinical epidemiology for the veterinarian - Villarroel, Aurora (Ames, Iowa, USA : Wiley Blackwell, 2015)
Practical Clinical Epidemiology for the Veterinarian provides thorough coverage of the fundamentals of epidemiological concepts, situated within the context of daily clinical practice. Examines epidemiology from the lens of daily clinical practice to offer a truly practical approach Demonstrates the relevance of epidemiology to clinical problems faced in the field using practical examples to clarify the concepts Includes clinical cases from all species, with an emphasis on small animal and equine medicine, to demonstrate the concepts Uses an easy-to-read approach, with graphs, flowcharts
Describing health and disease -- Basic epidemiology concepts -- Evidence-based medicine for the veterinarian -- Study designs -- Causation vs. association -- Diagnostic tests -- Outbreak investigations.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 08, 2015).
Keywords: Veterinary epidemiology; Communicable diseases in animals; Veterinary epidemiology; Veterinary medicine; Epidemiologic Methods -- veterinary; Disease Outbreaks -- veterinary; Evidence-Based Practice; Electronic books